Pelatihan Penerapan Fungsi-fungsi Manajemen dalam Pengelolaan Organisasi pada Pengurus Majelis Ta’lim Tulangan Sidoarjo - Fitri Astutik; Wahyu Eko Pujianto (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2024)
This service was carried out at the Tulangan Sidoarjo Ta'lim Council. The aim is to improve managerial knowledge and skills, transform the organization into an organization with professional management, and good employee performance, and increase social benefits. The training and mentoring approach with activity stages is one of the methods used to carry out activities. The stages are; A. How to implement, carry out, and manage organizational activities, b. training in making a good vision and mission, c and creating pamphlets to distribute on social media, such as organizational training and support activities. The benefit of this activity is that it can improve the managerial knowledge and work ethic of staff so they can manage the organization efficiently.